Development of Realistic Mathematics Learning Materials in Terms of Mathematical Literacy Skills - Faisol Hidayatulloh; M Farid Nasrulloh; Fitri Habibah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Mathematical literacy is very important. This is because mathematical literacy emphasizes the ability of students to analyze, argue about ideas effectively in solving mathematical problems they encounter (OECD, 2009, p.19). Judging from various things, the ministry of education and culture has actually anticipated it by making several curriculum changes. However, in the period 2000 until now there have been three types of curriculum that have been implemented, namely the 2004 curriculum, 2006 curriculum and 2013 curriculum. And by mastering students' mathematical literacy, individuals will be able to reflect on mathematical logic to play a role in their lives, communities, and society. Mathematical literacy makes individuals able to make decisions based on a constructive mathematical mindset. Realistic mathematics learning presents a contextual problem that can be related to local excellence-based educational games. The main goal is that students have high mathematical communication skills towards mathematics. Selin, the introduction of local excellence in educational games to students through learning that can be used as a way to grow the character of students to the local culture of the nation of Indonesia. Advances in technology and information that are not balanced with strong filters will affect the lifestyle of a foreign country. In this development using procedural development model. The development model in this study led to the development model of Sugiyono (2015). However, in this study not all steps are applied, this is because the research conducted is still on a limited scale with no cover into the wider research. Therefore it stages of development begins by doing 1. Planning with identification of potential problems, 2. Create a new design, 3. Validate the design, 4. Design revision, 5. Validate the design and the last 6. Product trials.